High-girth Steiner triple systems - Kwan, Matthew Alan; Sah, Ashwin; Sawhney, Mehtaab; Simkin, Michael (Annals of Mathematics)
We prove a 1973 conjecture due to Erdős on the existence of Steiner triple systems with arbitrarily high girth.

Reminiscences of a Real-Time Researcher - Henzinger, Thomas A (Real Time and Such)
I give a personal account about the wave of new research activities that rose in the 1990s on the specification, verification, and control of real-time systems.

Expansion properties of the young supernova type Iax remnant Pa 30 revealed - Cunningham, Tim; Caiazzo, Ilaria; Prusinski, Nikolaus Z.; Fuller, James; Raymond, John C.; Kulkarni, S. R.; Neill, James D.; Duffell, Paul; Martin, Chris; Toloza, Odette; Charbonneau, David; Kenyon, Scott J.; et al. (The Astrophysical Journal Letters)
The recently discovered Pa 30 nebula, the putative type Iax supernova remnant associated with the historical supernova of 1181 AD, shows puzzling characteristics that make it unique among known supernova remnants. In particular, Pa 30 exhibits a complex morphology, with a unique radial and filamentary structure, and it hosts a hot stellar remnant at its center, which displays oxygen-dominated, ultrafast winds. Because of the surviving stellar remnant and the lack of hydrogen and helium in its filaments, it has been suggested that Pa 30 is the product of a failed thermonuclear explosion in a near- or super-Chandrasekhar white dwarf, which created a subluminous transient, a rare subtype of the Ia class of supernovae called type Iax. We present here a detailed study of the 3D structure and velocities of a full radial section of the remnant. The Integral Field Unit observations, obtained with the new red channel of the Keck Cosmic Web Imager spectrograph, reveal that the ejecta are consistent with being ballistic, with velocities close to the free-expansion velocity. Additionally, we detect a large cavity inside the supernova remnant and a sharp inner edge to the filamentary structure, which coincides with the outer edge of a bright ring detected in infrared images. Finally, we detect a strong asymmetry in the amount of ejecta along the line of sight, which might hint at an asymmetric explosion. Our analysis provides strong confirmation that the explosion originated from SN 1181.

Mechanisms of visual integration and competition in innate behaviours in Drosophila melanogaster - Satapathy, Roshan K
Locomotion is ubiquitous in the animal kingdom because an animal's survival depends on its ability to navigate its environment to find food, avoid predators and locate potential mates. These behaviours require control mechanisms that can extract information from the environment, particularly visual cues. Selective evolutionary pressures have thus refined such visuomotor transformations in a species-specific manner to meet the specific ecological and ethological challenges of each organism. However, a common challenge across organisms as visual information processing becomes increasingly detailed is the mechanisms required to synthesise disparate pieces of information into a coherent percept or unified picture of the world. In this thesis, I investigate how disparate visual information is combined in the brain of Drosophila melanogaster to effectively guide locomotion. For this, I first designed and built a behavioural setup to record locomotion and present visual stimuli to freely-walking fruit flies in a closed-loop manner. This setup allowed the investigation of innate visually-guided behaviours, including the optomotor reflex and courtship. Second, taking advantage of my system I investigated the optomotor response, a reflexive visual stabilisation behaviour in which flies turn in the direction of global motion to minimise retinal slip. This behaviour is thought to be mediated by Lobula plate tangential cells (LPTCs); a complex network of optic-flow-sensitive neurons essential for self-motion estimation. Using a novel genetic mutant, I demonstrate that electrical coupling between two LPTC subtypes, contralateral HS and H2 neurons, regulates the balance between smooth optomotor turning and saccadic anti-optomotor responses. These findings underscore the critical role of binocular motion cue integration in guiding course control. Finally, I developed a novel behavioural paradigm in which a sexually aroused male fruit fly is presented with an optomotor distractor. This setup creates competition between two visual behaviours, courtship tracking and the optomotor response, enabling me to explore how the visual system resolves this conflict. In this setting, males engaged in courtship selectively suppress their optomotor response based on the female's location. Furthermore, when this experiment is replicated with an “artificial female”, optogenetically aroused males alternate between tracking and optomotor responses. The probability and dynamics of this switching are determined by the relative strengths of the two competing stimuli. In summary, the results presented in this thesis explore two mechanisms – integration and competition - through which visual information is combined in the brain of the fruit fly to drive locomotion.

A thalamic hub-and-spoke network enables visual perception during action by coordinating visuomotor dynamics - Vega Zuniga, Tomas A; Sumser, Anton L; Symonova, Olga; Koppensteiner, Peter; Schmidt, Florian; Jösch, Maximilian A
Electrophysiological, calcium two-photon recordings and behavioral data for Vega-Zuniga et al. Relevant information can be found in the 'README.txt' files.

Prolonged cultivation enhances the stimulatory activity of hiPSC mesenchymal progenitor-derived conditioned medium - Marolt Presen, Darja; Goeschl, Vanessa; Hanetseder, Dominik; Ogrin, Laura; Stetco, Alexandra Larissa; Tansek, Anja; Pozenel, Laura; Bruszel, Bella; Mitulovic, Goran; Oesterreicher, Johannes; Zipperle, Johannes; Schaedl, Barbara; et al. (Stem Cell Research and Therapy)
Background: Human induced pluripotent stem cells represent a scalable source of youthful tissue progenitors and secretomes for regenerative therapies. The aim of our study was to investigate the potential of conditioned medium (CM) from hiPSC-mesenchymal progenitors (hiPSC-MPs) to stimulate osteogenic differentiation of human bone marrow-derived mesenchymal stromal cells (MSCs). We also investigated whether prolonged cultivation or osteogenic pre-differentiation of hiPSC-MPs could enhance the stimulatory activity of CM. Methods: MSCs were isolated from 13 donors (age 20–90 years). CM derived from hiPSC-MPs was added to the MSC cultures and the effects on proliferation and osteogenic differentiation were examined after 14 days and 6 weeks. The stimulatory activity of hiPSC-MP-CM was compared with the activity of MSC-derived CM and with the activity of CM prepared from hiPSC-MPs pre-cultured in growth or osteogenic medium for 14 days. Comparative proteomic analysis of CM was performed to gain insight into the molecular components responsible for the stimulatory activity. Results: Primary bone marrow-derived MSC exhibited variability, with a tendency towards lower proliferation and tri-lineage differentiation in older donors. hiPSC-MP-CM increased the proliferation and alkaline phosphatase activity of MSC from several adult/aged donors after 14 days of continuous supplementation under osteogenic conditions. However, CM supplementation failed to improve the mineralization of MSC pellets after 6 weeks under osteogenic conditions. hiPSC-MP-CM showed greater enhancement of proliferation and ALP activity than CM derived from bone marrow-derived MSCs. Moreover, 14-day cultivation but not osteogenic pre-differentiation of hiPSC-MPs strongly enhanced CM stimulatory activity. Quantitative proteomic analysis of d14-CM revealed a distinct profile of components that formed a highly interconnected associations network with two clusters, one functionally associated with binding and organization of actin/cytoskeletal components and the other with structural constituents of the extracellular matrix, collagen, and growth factor binding. Several hub proteins were identified that were reported to have functions in cell-extracellular matrix interaction, osteogenic differentiation and development. Conclusions: Our data show that hiPSC-MP-CM enhances early osteogenic differentiation of human bone marrow-derived MSCs and that prolonged cultivation of hiPSC-MPs enhances CM-stimulatory activity. Proteomic analysis of the upregulated protein components provides the basis for further optimization of hiPSC-MP-CM for bone regenerative therapies.

Over 25 years of decrypting PIN-mediated plant development - Luschnig, Christian; Friml, Jiří (Nature Communications)
Identification of PIN exporters for auxin, the major coordinative signal in plants, some 25 years ago, signifies a landmark in our understanding of plant-specific mechanisms underlying development and adaptation. Auxin is directionally transported throughout the plant body; a unique feature already envisioned by Darwin and solidified by PINs’ discovery and characterization. The PIN-based auxin distribution network with its complex regulations of PIN expression, localization and activity turned out to underlie a remarkable multitude of developmental processes and represents means to integrate endogenous and environmental signals. Given the recent anniversary, we here summarize past and current developments in this exciting field.

Partitioning problems via random processes - Anastos, Michael; Cooley, Oliver; Kang, Mihyun; Kwan, Matthew Alan (Journal of the London Mathematical Society)
There are a number of well-known problems and conjectures about partitioning graphs to satisfy local constraints. For example, the majority colouring conjecture of Kreutzer, Oum, Seymour, van der Zypen and Wood states that every directed graph has a 3-colouring such that for every vertex v, at most half of the out-neighbours of v have the same colour as . As another example, the internal partition conjecture, due to DeVos and to Ban and Linial, states that for every d, all but finitely many d-regular graphs have a partition into two non-empty parts such that for every vertex v, at least half of the neighbours of v lie in the same part as v. We prove several results in this spirit: in particular, two of our results are that the majority colouring conjecture holds for Erdős–Rényi random directed graphs (of any density), and that the internal partition conjecture holds if we permit a tiny number of ‘exceptional vertices’. Our proofs involve a variety of techniques, including several different methods to analyse random recolouring processes. One highlight is a personality-changing scheme: we ‘forget’ certain information based on the state of a Markov chain, giving us more independence to work with.

Medium bands, mega science: A JWST/NIRCam medium-band imaging survey of A2744 - Suess, Katherine A.; Weaver, John R.; Price, Sedona H.; Pan, Richard; Wang, Bingjie; Bezanson, Rachel; Brammer, Gabriel; Cutler, Sam E.; Labbé, Ivo; Leja, Joel; Williams, Christina C.; Whitaker, Katherine E.; et al. (Astrophysical Journal)
In this paper, we describe the "Medium Bands, Mega Science" JWST Cycle 2 survey (JWST-GO-4111) and demonstrate the power of these data to reveal both the spatially integrated and spatially resolved properties of galaxies from the local Universe to the era of cosmic dawn. Executed in 2023 November, MegaScience obtained ∼30 arcmin2 of deep multiband NIRCam imaging centered on the z ∼ 0.3 A2744 cluster, including 11 medium-band filters and the two shortest-wavelength broadband filters, F070W and F090W. Together, MegaScience and the UNCOVER Cycle 1 treasury program provide a complete set of deep (∼28–30 magAB) images in all NIRCam medium- and broadband filters. This unique data set allows us to precisely constrain photometric redshifts, map stellar populations and dust attenuation for large samples of distant galaxies, and examine the connection between galaxy structures and formation histories. MegaScience also includes ∼17 arcmin2 of NIRISS parallel imaging in two broadband and four medium-band filters from 0.9 to 4.8 μm, expanding the footprint where robust spectral energy distribution (SED) fitting is possible. We provide example SEDs and multiband cutouts at a variety of redshifts, and use a catalog of JWST spectroscopic redshifts to show that MegaScience improves both the scatter and catastrophic outlier rate of photometric redshifts by factors of 2–3. Additionally, we demonstrate the spatially resolved science enabled by MegaScience by presenting maps of the [O iii] line emission and continuum emission in three spectroscopically confirmed z > 6 galaxies. We show that line emission in reionization-era galaxies can be clumpy, extended, and spatially offset from continuum emission, implying that galaxy assembly histories are complex even at these early epochs. We publicly release fully reduced mosaics and photometric catalogs for both the NIRCam primary and NIRISS parallel fields (jwst-uncover.github.io/megascience).

JWST FRESCO: A comprehensive census of H β + [O iii] emitters at 6.8 < z < 9.0 in the GOODS fields - Meyer, R. A.; Oesch, P. A.; Giovinazzo, E.; Weibel, A.; Brammer, G.; Matthee, Jorryt J; Naidu, R. P.; Bouwens, R. J.; Chisholm, J.; Covelo-Paz, A.; Fudamoto, Y.; Maseda, M.; et al. (Monthly Notices of the Royal Astronomical Society)
We present the census of Hβ+[OIII] 4960,5008 Åemitters at 6.8<z<9.0 from the JWST FRESCO survey over 124 arcmin2 in the GOODS-North and GOODS-South fields. Our unbiased spectroscopic search results in 137 spectroscopically-confirmed galaxies at 6.8<z<9.0 with observed [OIII] fluxes f[OIII]≳1×10−18 ergs s−1 cm−2. The rest-frame optical line ratios of the median stacked spectrum (median MUV=−19.65+0.59−1.05) indicate negligible dust attenuation, low metallicity (12+log(O/H)=7.2−7.7) and a high ionisation parameter log10U≃−2.5. We find a factor ×1.3 difference in the number density of 6.8<z<9.0 galaxies between GOODS-South and GOODS-North, which is caused by a single overdensity at 7.0<z<7.2 in GOODS-North. The bright end of the UV luminosity function of spectroscopically-confirmed [OIII] emitters is in good agreement with HST dropout-selected samples. Discrepancies between the observed [OIII] LF, [OIII]/UV ratio and [OIII] equivalent widths, and that predicted by theoretical models, suggest burstier star-formation histories and/or more heterogeneous metallicity and ionising conditions in z>7 galaxies. We report a rapid decline of the [OIII] luminosity density at z≳6−7 which cannot be explained by the evolution of the cosmic star-formation rate density. Finally we find that FRESCO detects in only 2h galaxies likely accounting for ∼10−20% of the ionising budget at z=7−8 (assuming an escape fraction of 10%), raising the prospect of directly detecting a significant fraction of the sources of reionisation with JWST.

The central limit theorem and rate of mixing for simple random walks on the circle - Czudek, Klaudiusz S; Dolgopyat, Dmitry (Alea)
We prove the Central Limit Theorem and superpolynomial mixing for environment viewed from the particle process in quasi periodic Diophantine random environment. The main ingredients are smoothness estimates for the solution of the Poisson equation and local limit asymptotics for certain accelerated walks.

Toward a common interpretation of the 3Rs principles in animal research - Lauwereyns, Jan; Bajramovic, Jeffrey; Bert, Bettina; Camenzind, Samuel; De Kock, Joery; Elezović, Alisa; Erden, Sevilay; Gonzalez-Uarquin, Fernando; Ulman, Yesim Isil; Hoffmann, Orsolya Ivett; Kitsara, Maria; Kostomitsopoulos, Nikolaos; et al. (Lab Animal)
Many scientific breakthroughs have depended on animal research, yet the ethical concerns surrounding the use of animals in experimentation have long prompted discussions about humane treatment and responsible scientific practice. First articulated by Russell and Burch, the 3Rs Principles of Replacement, Reduction, and Refinement have gained widespread recognition as basic guidelines for animal research. Over time, the 3Rs have transcended the research community, influencing policy decisions, animal welfare advocacy and public perception of animal experimentation. Despite their broad acceptance, interpretations of the 3Rs vary substantially, shaping statutory frameworks at various levels, with both technical and practical impacts.

Non equilibrium dynamics of driven individual particles and 3D printing across scales - Mweka, Cecelia N
This thesis is an experimental work about two distinct research projects that evolved from a single project: non-equilibrium dynamics of an acoustically vibrated particle and microfabrication of particles with nano-scale 3D printing. The first project explores non equilibrium dynamics of a particle driven by ultrasonic vibrations. We design an experimental system consisting of an electromechanical vibration scheme to drive the particle’s vibrations and an imaging scheme to track its trajectories. We study the trajectories to determine how the particle’s dynamics evolve under the driven conditions, considering out of equilibrium systems in the context of equilibrium statistical mechanics. Using a Langevin framework and the Boltzmann factor, we characterize the particle’s dynamics as complex; the particle motion is not purely diffusive. We extract physical parameters like spring constant, effective temperature, damping coefficient and resonance frequency. In the second project, we explore and develop techniques in the design and microfabrication of particles across scales. Microfabrication involves building structures at the micron or submicron scale. These designed miniaturized patterns, objects, or devices are useful in biophysics, pharmacology, medical biology, and nanotechnology. We specifically apply two-photon polymerization, a form of 3D nano printing. We print millimetric particles, characterizing different designs to evaluate and showcase the resolution, aspect ratio integrity and print quality of the printing process. We also design and fabricate a microsensor to deflect under applicable force of order 0.1 pN. We present fundamental concepts needed to design the microsensor, showcasing 3D printing at considerably smaller scales down to the µm or below.

A decoy receptor derived from alternative splicing fine-tunes cytokinin signaling in Arabidopsis - Králová, Michaela; Kubalová, Ivona; Hajný, Jakub; Kubiasova, Karolina; Vagaská, Karolína; Ge, Zengxiang; Gallei, Michelle C; Semerádová, Hana; Kuchařová, Anna; Hönig, Martin; Monzer, Aline; Kovačik, Martin; et al. (Molecular Plant)
Hormone perception and signaling pathways have a fundamental regulatory function in the physiological processes of plants. Cytokinins, a class of plant hormones, regulate cell division and meristem maintenance. The cytokinin signaling pathway is well established in the model plant Arabidopsis thaliana. Several negative feedback mechanisms, tightly controlling cytokinin signaling output, have been described previously. In this study, we identified a new feedback mechanism executed through alternative splicing of the cytokinin receptor AHK4/CRE1. A novel splicing variant named CRE1int7 results from seventh intron retention, introducing a premature termination codon in the transcript. We showed that CRE1int7 is translated in planta into a truncated receptor lacking the C-terminal receiver domain essential for signal transduction. CRE1int7 can bind cytokinin but cannot activate the downstream cascade. We present a novel negative feedback mechanism of the cytokinin signaling pathway, facilitated by a decoy receptor that can inactivate canonical cytokinin receptors via dimerization and compete with them for ligand binding. Ensuring proper plant growth and development requires precise control of the cytokinin signaling pathway at several levels. CRE1int7 represents a so-far unknown mechanism for fine-tuning the cytokinin signaling pathway in Arabidopsis.

Monitoring extended hypernode logic - Chalupa, Marek; Henzinger, Thomas A; Oliveira da Costa, Ana (Integrated Formal Methods)
Hypernode logic can reason about the prefix relation on stutter-reduced finite traces through the stutter-reduced prefix predicate. We increase the expressiveness of hypernode logic in two ways. First, we split the stutter-reduced prefix predicate into an explicit stutter-reduction operator and the classical prefix predicate on words. This change gives hypernode logic the ability to combine synchronous and asynchronous reasoning by explicitly stating which parts of traces can stutter. Second, we allow the use of regular expressions in formulas to reason about the structure of traces. This change enables hypernode logic to describe a mixture of trace properties and hyperproperties. We show how to translate extended hypernode logic formulas into multi-track automata, which are automata that read multiple input words. Then we describe a fully online monitoring algorithm for monitoring k-safety hyperproperties specified in the logic. We have implemented the monitoring algorithm, and evaluated it on monitoring synchronous and asynchronous versions of observational determinism, and on checking the privacy preservation by compiler optimizations.

Tools at the Frontiers of Quantitative Verification: QComp 2023 Competition Report - Andriushchenko, Roman; Bork, Alexander; Budde, Carlos E.; Češka, Milan; Grover, Kush; Hahn, Ernst Moritz; Hartmanns, Arnd; Israelsen, Bryant; Jansen, Nils; Jeppson, Joshua; Junges, Sebastian; Köhl, Maximilian A.; et al. (TOOLympics Challenge 2023)
The analysis of formal models that include quantitative aspects such as timing or probabilistic choices is performed by quantitative verification tools. Broad and mature tool support is available for computing basic properties such as expected rewards on basic models such as Markov chains. Previous editions of QComp, the comparison of tools for the analysis of quantitative formal models, focused on this setting. Many application scenarios, however, require more advanced property types such as LTL and parameter synthesis queries as well as advanced models like stochastic games and partially observable MDPs. For these, tool support is in its infancy today. This paper presents the outcomes of QComp 2023: a survey of the state of the art in quantitative verification tool support for advanced property types and models. With tools ranging from first research prototypes to well-supported integrations into established toolsets, this report highlights today’s active areas and tomorrow’s challenges in tool-focused research for quantitative verification.

Strong hole-photon coupling in planar Ge for probing charge degree and strongly correlated states - De Palma, Franco; Oppliger, Fabian; Jang, Wonjin; Bosco, Stefano; Janik, Marian; Calcaterra, Stefano; Katsaros, Georgios; Isella, Giovanni; Loss, Daniel; Scarlino, Pasquale (Nature Communications)
Semiconductor quantum dots (QDs) in planar germanium (Ge) heterostructures have emerged as front-runners for future hole-based quantum processors. Here, we present strong coupling between a hole charge qubit, defined in a double quantum dot (DQD) in planar Ge, and microwave photons in a high-impedance (Zr = 1.3 kΩ) resonator based on an array of superconducting quantum interference devices (SQUIDs). Our investigation reveals vacuum-Rabi splittings with coupling strengths up to g0/2π = 260 MHz, and a cooperativity of C ~ 100, dependent on DQD tuning. Furthermore, utilizing the frequency tunability of our resonator, we explore the quenched energy splitting associated with strong Coulomb correlation effects in Ge QDs. The observed enhanced coherence of the strongly correlated excited state signals the presence of distinct symmetries within related spin functions, serving as a precursor to the strong coupling between photons and spin-charge hybrid qubits in planar Ge. This work paves the way towards coherent quantum connections between remote hole qubits in planar Ge, required to scale up hole-based quantum processors.

Presynaptic cAMP-PKA-mediated potentiation induces reconfiguration of synaptic vesicle pools and channel-vesicle coupling at hippocampal mossy fiber boutons - Kim, Olena; Okamoto, Yuji; Kaufmann, Walter; Brose, Nils; Shigemoto, Ryuichi; Jonas, Peter M (PLoS Biology)
It is widely believed that information storage in neuronal circuits involves nanoscopic structural changes at synapses, resulting in the formation of synaptic engrams. However, direct evidence for this hypothesis is lacking. To test this conjecture, we combined chemical potentiation, functional analysis by paired pre-postsynaptic recordings, and structural analysis by electron microscopy (EM) and freeze-fracture replica labeling (FRL) at the rodent hippocampal mossy fiber synapse, a key synapse in the trisynaptic circuit of the hippocampus. Biophysical analysis of synaptic transmission revealed that forskolin-induced chemical potentiation increased the readily releasable vesicle pool size and vesicular release probability by 146% and 49%, respectively. Structural analysis of mossy fiber synapses by EM and FRL demonstrated an increase in the number of vesicles close to the plasma membrane and the number of clusters of the priming protein Munc13-1, indicating an increase in the number of both docked and primed vesicles. Furthermore, FRL analysis revealed a significant reduction of the distance between Munc13-1 and CaV2.1 Ca2+ channels, suggesting reconfiguration of the channel-vesicle coupling nanotopography. Our results indicate that presynaptic plasticity is associated with structural reorganization of active zones. We propose that changes in potential nanoscopic organization at synaptic vesicle release sites may be correlates of learning and memory at a plastic central synapse.

Removing popular faces in curve arrangements - De Nooijer, Phoebe; Terziadis, Soeren; Weinberger, Alexandra; Masárová, Zuzana; Mchedlidze, Tamara; Löffler, Maarten; Rote, Günter (Journal of Graph Algorithms and Applications)
A face in a curve arrangement is called popular if it is bounded by the same curve multiple times. Motivated by the automatic generation of curved nonogram puzzles, we investigate possibilities to eliminate the popular faces in an arrangement by inserting a single additional curve. This turns out to be NP-hard; however, it becomes tractable when the number of popular faces is small: We present a randomized FPT-time algorithm where the parameter is the number of popular faces.

Quantum scars make their mark in graphene - Abanin, Dmitry; Serbyn, Maksym (Nature)
By patterning an ultrathin layered structure with tiny wells, physicists have created and imaged peculiar states known as quantum scars — revealing behaviour that could be used to boost the performance of electronic devices.